Rumors and Conversations in Kazakh Village (Aul) on Eve of Famine (1927—1931) - N. N. Ablazhey; A. S. Zhanbossinova; E. E. Sailaubay (Научный диалог)
The social phenomenon of “rumors and gossip” in a Kazakh village during the 1920s-1930s is analyzed in this study. It is emphasized that rumors are an integral part of traditional society. It is asserted that the massive surge of rumors in Soviet Russia was a reaction of traditional society to forceful modernization. The goal of the article is to demonstrate the dichotomy of the content and form of rumors during the collectivization period in relation to the Kazakh village (aul). It is noted that the analytical materials of the OGPU are the most important source for studying the mood of the population of the USSR in the 1920s — early 1930s, which found reflection in rumors. It is shown that accelerated Sovietization generated a high level of anxiety in Kazakh society, reflected in the rise of apocalyptic moods and the actualization of mythology. The authors conclude that the idea of kiyamat was a form of deep protest of the village (aul), not an ideology of resistance. The form of active resistance in the republic is presented as mass migrations to China, which was due to the desire to “wait out” unstable times, so rumors about migrations were widely circulated in the borderlands. It is emphasized that rumors were an alternative view of Soviet reality, they slowed down the destruction of the village (aul) as a rural community and ensured the stability of traditional society.